Research in Finance - Chen, Andrew H. (Amsterdam : Elsevier, 2004)
Features papers that represent research on important topics in finance. This title includes contributions on analyses of issues relating to asset prices, the behaviour of stock returns, and capital-raising activities. It shows that the efficiency of time diversification depends on the degree of autocorrelation in security returns. A total of eleven papers in this volume represent recent research on important topics
includes bibliographical references.
opc 30/12/16, ijb 07/03/2019
Loans
Keywords: Finance; Finance and accounting